Инженерные основы проектирования камер сгорания авиационных ГТД: учебное пособие - Резник В. Е. Виктор Ефремович; Данильченко В. П. Валерий Павлович; Болотин Н. Б. Николай Борисович; Ковылов Ю. Л. Юрий Леонидович; Лукачев С. В. Сергей Викторович; Лукачев В. П. (Куйбышев, Изд-во КуАИ, 1981)
Авт. указаны на обороте тит. л.